2018
DOI: 10.1177/0003319718760916
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte to High-Density Lipoprotein Ratio Predicts Contrast-Induced Nephropathy in Patients With Acute Coronary Syndrome

Abstract: Contrast-induced nephropathy (CIN) is associated with worse prognosis in patients with acute coronary syndrome (ACS). Early identification and intervention for patients with a high risk of CIN are very important to improve clinical outcomes. Inflammation plays important role in the development of CIN in the setting of ACS. The monocyte to high-density lipoprotein ratio (MHR) is a novel inflammatory marker. Bleeding is also associated with worse prognosis in such patients. We aimed to investigate whether the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…Each marker, on its own, has been shown to be associated with in-hospital and/or long-term mortality (LTM) in patients with STEMI. 9 14 Although some reviews and meta-analyses focused on their effects on the prognosis in patients with CAD, little is known about their comparative predictive value. Therefore, in this study, we aimed to investigate which hematological indices have the most discriminatory capability for prediction of in-hospital and LTM in a large STEMI cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Each marker, on its own, has been shown to be associated with in-hospital and/or long-term mortality (LTM) in patients with STEMI. 9 14 Although some reviews and meta-analyses focused on their effects on the prognosis in patients with CAD, little is known about their comparative predictive value. Therefore, in this study, we aimed to investigate which hematological indices have the most discriminatory capability for prediction of in-hospital and LTM in a large STEMI cohort.…”
Section: Introductionmentioning
confidence: 99%
“…10 Many available biomarkers such as homocysteine, procalcitonin, high-sensitivity C-reactive protein, N-terminal pro-brain natriuretic peptide, red cell distribution width, neutrophil to lymphocyte ratio, platelet to lymphocyte ratio, monocyte to highdensity lipoprotein ratio, and fibrinogen to albumin ratio (FAR) have been shown to predict CIN development. [11][12][13][14][15][16][17][18][19] In the study by Yildiz et al, 1 serum osmolarity, hemoglobin, contrast media volume, creatinine on admission, basal SYNergy between PCI with TAXus and cardiac surgery II score, and left ventricular ejection fraction were found to be independent predictors of CIN. However, serum osmolarity only had a modest predictive accuracy for CIN in this analysis.…”
mentioning
confidence: 95%
“…10 Many available biomarkers such as homocysteine, procalcitonin, high-sensitivity C-reactive protein, N-terminal pro-brain natriuretic peptide, red cell distribution width, neutrophil to lymphocyte ratio, platelet to lymphocyte ratio, monocyte to high-density lipoprotein ratio, and fibrinogen to albumin ratio (FAR) have been shown to predict CIN development. 11 19…”
mentioning
confidence: 99%
“…The clinical trials conducted in recent years have shown that monocyte/HDL ratio (MHR) might be a new marker of inflammation 10,11 . Previous studies that claimed that, MHR may be related with the risk of contrast nephropathy development and monocyte and HDL cholesterol levels of patients with CKD may be used to predict their cardiovascular events 12,13 . This cross-sectional study aims to compare MHR levels of patients who have HD and PD as renal replacement therapy.…”
Section: Introductionmentioning
confidence: 99%